Oil price shocks, sectoral Co2 emissions and financial development in Malaysia - Maji, Ibrahim Kabiru (2017)
The study investigates the impact of oil price shocks and financial development on key economic indicators and sectoral carbon dioxide (CO2) emissions in Malaysia. The first objective examines the impact of recent oil price shocks on government revenue, Gross Domestic Product (GDP) and employment. Fixed proportions production theory of Leontief 1936 was used as the theoretical framework while a high bride econometric and input-output analysis were used as the empirical model. Augmenting a time-series data with the latest 2010 Malaysia’s input-output table is a contribution to knowledge. The result shows that the annual average decline in crude oil price by 48.4% between 2014 and 2015 has led to decline in government revenues by about 11.7 billion Ringgit (RM) and a fall in GDP by RM14.8 billion. Furthermore, based on Malaysia’s government budget recalibration of 2016, the result shows that oil price fall by 39.6% from 2015 benchmarks. This led to a decline in 2016 tax revenues by RM5.4 billion and a GDP loss of about RM6.5 billion. The results also suggest that GDP is projected to growth at about 3.9% - 4.1%. This is consistent with Malaysia’s Bank Negara release of the second quarter report for 2016, which project GDP growth at 4.0%. As such, the study recommends that policymakers should take proactive measure to further diversify the economy by promoting manufacturing and services sectors which were also identified as drivers of the economy. The second objective examines the impact of oil price shocks on sectoral CO2 emissions in Malaysian. The linearized Environmental Kuznets Curve (EKC) theory was employed as the theoretical framework of the study while Autoregressive Distributed Lag (ARDL) bounds approach was used as the empirical framework. Dynamic Ordinary Least Squares (DOLS) and Ordinary Least Squares (OLS) with robust standard error were used to further validate the results. The datasets range from 1983-2014. Extending the impact of oil price changes to sectoral CO2 emissions is not common in literature. The long-run results revealed an inverse relationship between oil price shocks and sectoral CO2 emissions and CO2 emissions per capita for all the three estimators. This suggests that higher oil price mitigates sectoral CO2 emissions and lower oil price increases sectoral CO2 emissions in Malaysia. On the average, the longrun impact of income on sectoral and per capita CO2 emissions is positive, indicating that an increase in the level of income increases both the sectoral and per capita CO2 emissions. Furthermore, the level of capital mitigates both sectoral and per capita CO2 emissions in Malaysia. Similarly, the result on the average, suggests that labour force also mitigates CO2 emissions and improves environmental quality. Thus, the study recommends contractionary fiscal measures on oil related products during lower oil prices. The third objective assesses the impact of financial development on sectoral CO2 emissions in Malaysia. The theoretical framework used was the linear version of EKC theory. The empirical model is ARDL while DOLS and OLS with robust standard error were used to verify the results. The datasets employed range from 1980- 2014. Extending the impacts of financial development to sectoral CO2 emissions is one of the contributions of this study. The consistent long-run results for all the estimators suggest that financial development invokes CO2 emissions in the transportation sector, oil and gas sector and per capita CO2 emissions. On the other hand, financial development mitigates CO2 emissions from the manufacturing and construction sector but does not impact on CO2 emissions from the agricultural sector. On the average, the results show that financial development increases CO2 emissions and reduces environmental quality in Malaysia. Thus, the study recommends that government should pay attention to abatement policies of the manufacturing and construction sector along with an emphasis on energy conservation measures and their efficient utilisation.